The History of the Irish Famine - Kinealy, Christine. (Milton)
1 online resource (320 pages)
Keywords: The Great Irish Famine remains one of the most lethal famines in modern world history and a watershed moment in the development of modern Ireland - socially, politically, demographically and culturally. In the space of only four years, Ireland lost twenty-five per cent of its population as a consequence of starvation, disease and large-scale emigration. Certain aspects of the Famine remain contested and controversial, for example the issue of the British government's culpability, proselytism, and the reception of emigrants. However, recent historiographical focus on this famine has overshadowed the impact of other periods of subsistence crisis, both before 1845 and after 1852.This volume seeks to counterbalance the recent historiographical focus on the Great Irish Famine which has overshadowed the impact of other periods of subsistence crisis, both before 1845 and after 1852. As occurred during the Great Famine, they often resulted in increased levels of evictions, emigration, disease and death, although the scale was lower.